2014
DOI: 10.1073/pnas.1323073111
|View full text |Cite|
|
Sign up to set email alerts
|

Shifts in flowering phenology reshape a subalpine plant community

Abstract: Phenology-the timing of biological events-is highly sensitive to climate change. However, our general understanding of how phenology responds to climate change is based almost solely on incomplete assessments of phenology (such as first date of flowering) rather than on entire phenological distributions. Using a uniquely comprehensive 39-y flowering phenology dataset from the Colorado Rocky Mountains that contains more than 2 million flower counts, we reveal a diversity of species-level phenological shifts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
623
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(662 citation statements)
references
References 44 publications
31
623
7
1
Order By: Relevance
“…I found a wide range of flowering time temperature-sensitivity among the seven species, with mountain avens being the most temperature-sensitive. The diversity of flowering time temperature-sensitivity in my elevation gradient study concurs with my herbarium specimen study findings and further supports my hypothesis of altered Arctic ecological community structure with climate change (CaraDonna et al, 2014). As with the Tanquary Fiord long-term phenology monitoring study, I found that the flowering time temperature-sensitivity of mountain avens was twice that of purple saxifrage, and that seed dispersal times of mountain avens showed temperature-sensitivity, while those of purple saxifrage did not.…”
Section: Elevation Gradient Studysupporting
confidence: 81%
See 1 more Smart Citation
“…I found a wide range of flowering time temperature-sensitivity among the seven species, with mountain avens being the most temperature-sensitive. The diversity of flowering time temperature-sensitivity in my elevation gradient study concurs with my herbarium specimen study findings and further supports my hypothesis of altered Arctic ecological community structure with climate change (CaraDonna et al, 2014). As with the Tanquary Fiord long-term phenology monitoring study, I found that the flowering time temperature-sensitivity of mountain avens was twice that of purple saxifrage, and that seed dispersal times of mountain avens showed temperature-sensitivity, while those of purple saxifrage did not.…”
Section: Elevation Gradient Studysupporting
confidence: 81%
“…For each species separately, I ran a regression analysis of the flowering time records with the associated June mean temperature over the last 70 years (1946 -2015) to determine the flowering time temperature-sensitivity of each of the 23 plant species. I found great diversity in the flowering time temperature-sensitivity of the 23 species (Panchen and Gorelick, in press), and I suggested that the interspecific variation in responsiveness to climate change could lead to altered Arctic ecological community competition, pollinator interactions, and ultimately Arctic ecological community composition (Hegland et al, 2009;McKinney et al, 2012;CaraDonna et al, 2014). The flowering time temperature-sensitivity also varied within a species: for example, plants from the Nunavut archipelago (includes the Boothia and Melville Peninsulas, as well as islands north of Hudson Bay) were more temperature-sensitive than their conspecifics from mainland Nunavut farther south (includes islands with similar latitude and climate), and within the Nunavut archipelago, plants from Baffin Island were more temperature-sensitive than their conspecifics from Ellesmere Island.…”
Section: Herbarium Specimen Studymentioning
confidence: 99%
“…During the peak summer season in July, which corresponds roughly to the peak in density of wildflowers of all species (CaraDonna et al 2014), the counts must greatly exceed these averages, since the averages include periods of much lower use in spring and autumn. A noticeable plume of dust trails each vehicle ( fig.…”
mentioning
confidence: 99%
“…2011;Cook et al 2012;Wolkovich et al 2012;Wang et al 2014a). Plants may face trade-offs between the adjustment of one phenological event to temperature and the timing of subsequent events during the growing season (Post et al 2008;Sherry et al 2007Sherry et al , 2011 Haggerty and Galloway 2011; Dorji et al, 2013;CaraDonna et al 2014;Wang et al 2014b). This is illustrated by Fig.…”
mentioning
confidence: 99%